Factors influencing thrombectomy decision making for primary medium vessel occlusion stroke. (4th May 2021) - Cimflova, Petra; Kappelhof, Manon; Singh, Nishita; Kashani, Nima; Ospel, Johanna Maria; McDonough, Rosalie; Demchuk, Andrew M; Menon, Bijoy K; Sakai, Nobuyuki; Chen, Michael; Fiehler, Jens; Goyal, Mayank
Abstract : Background: We aimed to explore the preference of stroke physicians to treat patients with primary medium vessel occlusion (MeVO) stroke with immediate endovascular treatment (EVT) in an international cross-sectional survey, as there is no clear guideline recommendation for EVT in these patients. Methods: In the survey MeVO-Finding Rationales and Objectifying New Targets for IntervEntional Revascularization in Stroke (MeVO-FRONTIERS), participants were shown four cases of primary MeVOs (six scenarios per case) and asked whether they would treat those patients with EVT. Multivariable logistic regression with clustering by respondent was performed to assess factors influencing the decision to treat. Dominance analysis was performed to assess the influence of factors within the scenarios on decision making. Results: Overall, 366 participants (56 women; 15%) from 44 countries provided 8784 answers to 24 scenarios. Most physicians (59.2%) would treat patients immediately with EVT. Younger patient age (incidence rate ratio (IRR) 1.24, 99% CI 1.19 to 1.30), higher National Institutes of Health Stroke Scale (NIHSS) score (IRR 1.69, 99% CI 1.57 to 1.82), and small core volume (IRR 1.35, 99% CI 1.24 to 1.46) were positively associated with the decision to treat with EVT. Interventionalists (IRR 1.26, 99% CI 1.01 to 1.56) were more likely to treat patients with MeVO immediately with EVT. In the dominance analysis, factors influencing the decision in favor of EVT were (in order of importance): baseline NIHSS, core volume, alteplase use, patients' age, and occlusion site. Conclusions: Most physicians in this survey were interventionalists and would treat patients with MeVO stroke immediately with EVT. This finding supports the need for robust clinical evidence.